Impact of work environment on job satisfaction and stress among hemodialysis staff in Klang Valley - Yusuf Zaima Mat; Yee Bit Lian (Sciendo, 2023)
To investigate the factors contributing to satisfaction with the work environment, job satisfaction (JS), and stress among hemodialysis (HD) staff in the central region of Malaysia.